Remote cerebellar haemorrhage: A case report - Kumar, Sachin; Kale, Hrishikesh A (Indian Journal of Radiology and Imaging, 2020)
Intracranial haemorrhage after supra-tentorial craniotomies can occur in a typical pattern and location which may suggest the diagnosis of remote cerebellar haemorrhage (RCH) which is quite a rare occurrence. The ‘Zebra Sign’ refers to a pattern of hyperdensity indicative of blood and hypodensity indicative of normal cerebellar parenchyma in a curvilinear, stripe-like fashion along the cerebellar folia and is a characteristic imaging finding in RCH. RCH in general doesn’t require surgical treatment, however in cases of significant hydrocephalus or progressive deterioration of consciousness surgical treatment may be warranted. The knowledge of this condition is important as it can pre-empt unnecessary further investigations and biopsy. Although imaging appearance may be striking, close imaging follow-up and clinical monitoring are often enough for the management of this entity.
Keywords: Cerebellum; craniotomy; intracranial hemorrhages; postoperative complications